2010
DOI: 10.1021/es901971a
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability of Nanoscale Metal Oxides TiO2, CeO2, and ZnO to Fish

Abstract: Nanoparticles (NPs) are reported to be a potential environmental health hazard. For organisms living in the aquatic environment there is much uncertainty on exposure because of a fundamental lack of understanding and data regarding the fate, behavior and bioavailability of the nanomaterials in the water column. This paper reports on a series of integrative biological and physicochemical studies on the uptake of unmodified commercial nanoscale metal oxides, zinc oxide (ZnO), cerium dioxide (CeO 2 ), and titaniu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
130
1
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 259 publications
(135 citation statements)
references
References 43 publications
3
130
1
1
Order By: Relevance
“…Results with this technique indicated that there was no detectable uptake of SWNTs by clams after exposure for 10 d to sediment concentrations of 0.03 g/kg, a result that was confirmed by TEM. Coherent anti-Stokes Raman scattering microscopy was also recently used to investigate the absorption of a range of metal and metal oxide nanoparticles in fish [101].…”
Section: Methods Of Cnp Analysis In Other Matricesmentioning
confidence: 99%
“…Results with this technique indicated that there was no detectable uptake of SWNTs by clams after exposure for 10 d to sediment concentrations of 0.03 g/kg, a result that was confirmed by TEM. Coherent anti-Stokes Raman scattering microscopy was also recently used to investigate the absorption of a range of metal and metal oxide nanoparticles in fish [101].…”
Section: Methods Of Cnp Analysis In Other Matricesmentioning
confidence: 99%
“…The finding for silver in the gastrointestinal tract would suggest that the fish took up the silver particles through drinking or ingesting aggregates of silver particles that formed in the tanks. In some of our previous work we have reported that fish exposed to CeO 2 via the water take up aggregated material via ingestion [14]. The results from the fish exposures further indicate that Ag particles (or silver ions derived from particles at the cell surface) were able to translocate from the fish gastrointestinal tract to other organs, leading to their accumulation in the liver and gallbladder.…”
Section: Particle Uptakementioning
confidence: 82%
“…Investigations with Daphnia magna have shown that 20 and 1,000 nm fluorescent polystyrene particles are rapidly taken up into the gastrointestinal tract, from where they are translocated to lipid storage droplets [13]. Uptake of TiO 2 and Ag NPs into fish has been demonstrated both by ingestion and across the gills through water [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Raman spectroscopy can provide a phenotypic fingerprint of constituent biomolecules without the need for labelling or staining. The fine spatial scale mapping ability of Raman, particularly Coherent anti-Stokes Raman spectroscopy (CARS), has successfully been used to localize metal oxide nanoparticles in tissues (Moger et al, 2008;Galloway et., 2010;Johnston et al, 2010). Here we utilized the ability of Raman spectroscopy to generate fingerprints from biological tissues to identify changes in the biomolecular phenotype in control and ZnONP exposed wild-type and mtl-1;mtl-2;pcs-1(zs2) nematodes.…”
Section: Resultsmentioning
confidence: 99%